Influence of Informal Relationships on Expatriate Career Performance in China: The Moderating Role of Cultural Intelligence. (July 2020) - Ren, Shuang; Chadee, Doren; Presbitero, Alfred
ABSTRACT: Pursuing an international career in China can be risky particularly when there is a lack of informal relationships and knowledge of the socio-cultural environment of the country. Drawing from social capital theory of career success and intelligence theory, this study investigates the influence of expatriate manager-local subordinate guanxi on expatriate managers' career performance and the contingency role of cultural intelligence. Using multi-source data from a sample (N = 154) of expatriate managers in China, our results show that expatriate manager-local subordinate guanxi positively influences expatriate career performance, and that this relationship is positively moderated by expatriates' cultural intelligence. The broader theoretical and practical implications of the findings for international careers are fully discussed.